Integrating Religiosity and Public Policy to Foster Green Behavior: A Muslim Perspective - Al Hadi, Qoshid (Journal of Islamic Economic Laws, 2025)
Plastic pollution has become one of the most pressing environmental challenges of our time, yet the role of faith and knowledge in driving sustainable consumer behavior remains underexplored. This study investigates how   religiosity, green knowledge, and plastic ban policies interact to shape green behavior among Muslim consumers. By integrating the Norm Activation Theory (NAT) and Institutional Theory, it develops a novel framework for understanding sustainability within a religious context. A survey of 210 Muslim consumers in Banjarmasin, Indonesia, was conducted using a five-point Likert scale to measure green knowledge, religiosity, perceptions of plastic ban policies, and green behavior, with data analyzed through structural equation modeling (SEM) to assess causal relationships. The results show that green knowledge is a strong predictor of green behavior, reinforcing personal norms aligned with Islamic values. In contrast, religiosity demonstrates a negative association with green behavior, reflecting barriers such as higher costs and limited access to eco-friendly products. Plastic ban policies strengthen social norms but, when interacting with religiosity, reduce individual responsibility. The originality of this study lies in its integration of religious values into NAT and Institutional Theory, providing new insights into how personal norms and institutional pressures interact to drive sustainability. The study is limited by its reliance on self-reported data and a localized sample, and future research is encouraged to expand to cross-cultural contexts and incorporate observed behavioral data.